Ukuran Perusahaan, Tipe Industri, dan Kualitas Pengungkapan Sustainable Development Goals - Saraswati Devi, Nyoman Radhika; Dwi Ratnadi, Ni Made (E-Jurnal Akuntansi; Vol 34 No 10 (2024)DO - 10.24843/EJA.2024.v34.i10.p05, 2024)
The sustainable development goals (SDGs) are a series of sustainable development objectives established to achieve a better life. The role of companies in Indonesia in achieving these goals can be realized by disclosing the SDGs in their sustainability reports. The quality of SDG disclosure can be assessed based on the topics disclosed in accordance with the GRI Standards guidelines, as well as the presentation format. The aim of this research is to empirically examine the influence of company size and industry type on the quality of SDG disclosure. This research was conducted on companies listed on the Indonesia Stock Exchange in 2023. The research sample consists of 183 companies obtained using nonprobability sampling and purposive sampling techniques. The data analysis technique used is multiple linear regression analysis. The analysis results show that company size and industry type have a positive influence on the quality of SDG disclosure. The research implications confirm the legitimacy theory and political cost hypothesis.